LAWS OF TRANSPORT CONGESTION ON THE ROAD NETWORK CITIES - Stepanchuk, Olexander; Bieliatynskyi, Andrii; Timkina, Svitlana (Proceedings of National Aviation University (archive), 2016)
Purpose: In the first place among the urban transport problems by its importance is the issue of the capacity of city streets and roads. There are the contradictions that arised in the movement of the traffic on city streets, creating a corresponding complexity of their functioning. Mutual influence of pedestrians on vehicular traffic and vice versa, as well as the needness to ensure the safety of city traffic conditions are required the introduction of restrictive and prohibitive measures which, in turn, affect the speed of the transport streams and the capacity of road network. Methods: To analyze the patterns of occurrence of congestion on main streets and perform a theoretical study of measures aimed at improving the efficiency of the road network of the city. Results: We revealed laws of occurrence of congestion on main streets, set the list of obstacles that cause delay the movement of vehicles on the road network of the city and their frequency. Discussion: The main focus for solving the problems of traffic congestion occurrence should be a system of regulating system correlation of demand on the trip and suggestions as street and road infrastructure with the purpose of its loading at the acceptable level.